Mosque-Based Islamic Education for Converts Through Community-Centered Programs - Annisa Nursyifa; Zulfiana Herni (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Mosques serve not only as places of worship but also hold potential as educational hubs, particularly in areas with high religious learning needs. Specific Background: Kampung Muallaf, home to many new converts, reflects a critical need for structured Islamic education. Knowledge Gap: Despite the significance of mosques in religious education, limited studies explore their pedagogical roles in muallaf communities. Aims: This study aims to investigate the mosque’s role as a center for Islamic education, identify existing educational activities, and assess the supporting and inhibiting factors in Kampung Muallaf. Results: Findings reveal that the mosque functions as a hub for Qur’anic learning, da’wah, religious training, and social cohesion. Key educational activities include MDTA programs, wiridan, recitations, and convert coaching. Support is driven by active da’wah teams, while lack of parental encouragement hinders youth participation. Novelty: The study highlights a holistic educational model tailored for converts, integrating worship, learning, and community support. Implications: These insights inform mosque-based educational strategies and policymaking to better serve marginalized religious communities. Highlights: Highlights the mosque’s role beyond worship—as an Islamic education hub. Identifies structured programs for converts and local community engagement. Reveals key support and barriers in sustaining religious learning activities. Keywords: Mosque Education, Kampung Muallaf, Islamic Learning, Religious Practice, Community Da’wah